Relief Medallions as a source of inspiration for artistic creations utilising wood waste - Yuliana, Tri; Meilinda, Vina; Rohmawati, Fauziah Dwi (Universitas Negeri Yogyakarta, 2025)
In recent times, local culture has begun to be displaced by modernisation, and environmental awareness has declined. Therefore, efforts are needed to revive love for local culture and the environment. The purpose of this study is to create artwork with themes of local culture and the environment, namely, medallion reliefs and wood waste. Artwork featuring themes of local culture and the reuse of waste is one of the efforts to introduce, preserve, and conserve local culture and the environment through art. The research method employs Arts-Based Research. The artistic practice follows a three-stage experimental sequence: the exploration stage, the design stage, and the realisation stage. The results of this research indicate that wood waste has high potential for being utilised as an alternative medium for creating artworks. The result of this creative process is an environmentally friendly and affordable collage artwork themed around a medallion. _______________________________________________________________________________ Beberapa waktu terakhir budaya lokal mulai tergeser oleh modernisasi, dan kecintaan terhadap lingkungan mengalami kemerosotan. Sehingga dibutuhkan suatu upaya untuk menumbuhkan kembali kecintaan budaya lokal dan lingkungan. Tujuan penelitian ini ialah untuk menciptakan karya seni dengan tema budaya lokal dan berbasis lingkungan yakni relief medalion dan limbah kayu. Karya seni dengan tema budaya lokal dan pemanfaatan limbah menjadi salah satu upaya untuk mengenalkan, menjaga dan melestarikan budaya lokal dan lingkungan melalui karya seni. Metode penelitian memakai Arts based Research. Praktek artistik menggunakan urutan eksperimen tiga tahap, yaitu: tahap eksplorasi, tahap perancangan, dan tahap perwujudan. Hasil dari penelitian ini menunjukan bahwa limbah kayu memiliki pontensi tinggi untuk dimanfaatkan menjadi alternatif medium penciptaan karya seni. Hasil proses kreatif ini yaitu karya seni kolase bertema medalion yang ramah lingkungan dan terjangkau.